Intervensi Perilaku Perundungan pada Siswa Sekolah Dasar sebagai Pelaku - Amelia Hanifa Iswan; Lucia R. M. Royanto (Jurnal Psikologi Teori dan Terapan, 2019)
This study examines the effectiveness of an anti-bullying training program for elementary school bullies. The training program provides knowledge about bullying as well as various activities that can improve the ability of empathy and self-control and decrease bullying behaviors. A quasi-experiment with one-group pretest-and-posttest design was employed. Fifteen student bullies from the grades 5A and 5B  of a private Elementary School ˜X were recruited based on the results of teachers interviews, students sociometry and focus group discussions (FGD). Data were collected using empathy scale and Peer Interaction in Primary School Questionnaire. Qualitative data were also collected from participants and their teachers using interviews and FGD. Data on bullying behavior and empathy were analyzed using paired sample t-tests, while knowledge of bullying and self control were analyzed qualitatively. The result of t-test shows that the effect of the anti-bullying training is not significant. However, results from qualitative analysis show that participants' knowledge about bullying has increased and bullying behaviors of participants, primarily among students of class 5B, have decreased. In contrast, bullying behaviors of participants from the class 5A remain unchanged. The ways the homeroom teachers use to manage both classrooms determine the changes in bullying behaviors.Keywords: Bullying, training, empathy, self-control, primary school students